2020
DOI: 10.36902/sjesr-vol3-iss1-2020(57-66)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resilience Intervention on Levels of Optimism

Abstract: This study explores the impact of 3-weeks intervention based on resilience as a psychosocial skill to enhance the levels of optimism, self-esteem, and resilience as well as the correlation between these variables. Participants were selected randomly from the Law College studying in Undergraduate Program. The intact group received 3 two-hours weekly sessions. Measures of Life Orientation Test (Revised), resilience scale and self-esteem scale were administered to gauge pre-post intervention. Data analysis indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In this line of reasoning, it is important to enhance nurses' resilience in order to have good expectations about their future. This result went on the same line with the study approved by Bhatti et al, (2020) (6) who revealed that, the resilience intervention successfully increased their levels of optimism in their lifeorientation by widening their vision to perceive possibilities and alternative explanations for the Vol. 25.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In this line of reasoning, it is important to enhance nurses' resilience in order to have good expectations about their future. This result went on the same line with the study approved by Bhatti et al, (2020) (6) who revealed that, the resilience intervention successfully increased their levels of optimism in their lifeorientation by widening their vision to perceive possibilities and alternative explanations for the Vol. 25.…”
Section: Resultssupporting
confidence: 86%
“…This result may be due to that, more stress resiliency and coping techniques have been reported to be associated with optimism (31) . This interpretation is supported by Bhatti et al, (2020) (6) who illustrated that internal strength that promotes positive changes through and after distress and actively seeks meaning and purpose in life is referred to as resilience. This supports the premise that a human's ability to respond positively to adversity is known as resilience (32) .In this light, it is critical to promote nurses' optimism in order to improve their chances of dealing with obstacles in a more adaptable manner.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Failure of pessimistic depressed patients to participate in treatment exacerbates their medical problems, jeopardizes their health, and ultimately leads to their premature death 19 . Considering the high prevalence of depression and the significant burden this disease places on individuals, the healthcare system, and society, it is necessary to conduct comprehensive studies to develop appropriate methods for the prevention, treatment, and management of this disease 20 . Considering that the treatment and control of major depression improves the quality of life, enables the return to society, and promotes patient communication, we decided to conduct a study to determine the average self-esteem and optimism of patients suffering from depression in 2022.…”
Section: Introductionmentioning
confidence: 99%